Analysis of Pharmaceutical Plant Location Design in Cities - Yuze Gao (Innovation in Science and Technology, 2023)
In the contemporary era, heightened by China’s advancing national prowess and improved living standards, health concerns have gained prominence in societal discourse. While medicine is instrumental in preserving health, the impact of pollution from pharmaceutical processes, particularly wastewater, poses health risks. Consequently, judiciously siting pharmaceutical plants assumes paramount importance. China is currently in the nascent stage of pharmaceutical plant location, lacking a comprehensive practice. Selecting an appropriate site efficiently remains a critical challenge. This paper advocates the Analytic Hierarchy Process (AHP) as a superior method for this purpose. Considering environmental and economic factors, it introduces indicators like environmental functional zoning, sensitivity, traffic, meteorological disasters, and local economic development. The AHP model quantitatively analyzes these factors, determining optimal locations through weight distribution and consistency indicators. This approach offers a systematic framework for pharmaceutical plant location planning.